2020
DOI: 10.1242/dmm.044727
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of CCR4-NOT complex subunits affects heart structure and function

Abstract: The identification of genetic variants that predispose individuals to cardiovascular disease and a better understanding of their targets would be highly advantageous. Genome-wide association studies have identified variants that associate with QT-interval length (a measure of myocardial repolarization). Three of the strongest associating variants (single-nucleotide polymorphisms) are located in the putative promotor region of CNOT1, a gene encoding the central CNOT1 subunit of CCR4-NOT: a multifunctional, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…Across the hGWAS set of 40 genes, comparative heart rate analysis showed statistically significant heart rate phenotypes in a total of 16 genes ( Fig 3B). The five positive controls, known to play key roles in heart functions such as cardiac contraction (TTN and NACA) and heart rate regulation (CASQ2, Beyond known cardiac genes, we revealed new genes linked to various biological functions (CCDC141, GIGYF1, HOMEZ, MYRF, SMG6, CMYA5, CNOT1, SLC17A3, TRAPPC12, SSPO and PADI4) which up to now, had little to no experimental evidence in cardiac function (Rathjens et al 2020;Benson et al 2017;Yamaguchi et al 2018;Elmen et al 2020).…”
Section: Resultsmentioning
confidence: 97%
“…Across the hGWAS set of 40 genes, comparative heart rate analysis showed statistically significant heart rate phenotypes in a total of 16 genes ( Fig 3B). The five positive controls, known to play key roles in heart functions such as cardiac contraction (TTN and NACA) and heart rate regulation (CASQ2, Beyond known cardiac genes, we revealed new genes linked to various biological functions (CCDC141, GIGYF1, HOMEZ, MYRF, SMG6, CMYA5, CNOT1, SLC17A3, TRAPPC12, SSPO and PADI4) which up to now, had little to no experimental evidence in cardiac function (Rathjens et al 2020;Benson et al 2017;Yamaguchi et al 2018;Elmen et al 2020).…”
Section: Resultsmentioning
confidence: 97%
“…Some of the strongest QT-associating variants identified, centre around the CNOT1 gene. Using reporter assays it was shown that reduced CNOT1 expression contributes to abnormal QT-intervals [402]. Cardiac specific depletion of Not1 and Pop2 in Drosophila was either lethal or resulted in dilated cardiomyopathy, reduced contractility, or a propensity for arrhythmia [186,402].…”
Section: The Cnot Complex and Human Diseasementioning
confidence: 99%
“…Using reporter assays it was shown that reduced CNOT1 expression contributes to abnormal QT-intervals [402]. Cardiac specific depletion of Not1 and Pop2 in Drosophila was either lethal or resulted in dilated cardiomyopathy, reduced contractility, or a propensity for arrhythmia [186,402]. Similarly, the loss of Not2, Not3, Not4 and twin affected cardiac chamber size and contractility [186,402].…”
Section: The Cnot Complex and Human Diseasementioning
confidence: 99%
See 1 more Smart Citation
“… ABSTRACT First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Lisa Elmén is first author on ‘ Silencing of CCR4-NOT complex subunits affects heart structure and function ’, published in DMM. Lisa conducted the research described in this article while a lab manager/research associate in Rolf Bodmer's lab at Sanford Burnham Prebys Medical Discovery Institute, La Jolla, CA, USA.…”
mentioning
confidence: 99%